Assessing the Long‐Term Survival of Dental Implants in A Retrospective Analysis: Immediate Versus Delayed Placement - Georgios S. Chatzopoulos; Larry F. Wolff (Clinical and Experimental Dental Research)
ABSTRACT Objectives This large‐scale retrospective study aims to evaluate and compare the long‐term survival rates of dental implants placed immediately after tooth extraction (type 1) versus those placed at a later stage (types 2, 3, and 4). Additionally, it examines how patient characteristics and implant site conditions influence the choice of implant placement. Materials and Methods This study retrospectively analyzed patient data from 10 university dental clinics between 2011 and 2022 and examined dental implant treatment outcomes. Patient information, including age, sex, ethnicity, race, smoking, and medical status, was analyzed. Results Records of 20,842 patients with 50,333 dental implants inserted between 2011 and 2022 were analyzed. The multivariate analysis resulted in significant differences for age, ethnicity, race, gender, and asthma. A 98.4% survival rate for dental implants placed immediately following extraction and a 98.6% survival rate for those placed in fully healed sockets were recorded. The type of implant placement (immediate vs. delayed) showed no significant effect on implant outcome. Conclusion Immediate implant placement resulted in high survival rates with delayed implants inserted into healed sites. Both immediate and delayed implant placements are viable therapeutic approaches demonstrating predictable outcomes.